2022
DOI: 10.1001/jamainternmed.2022.3858
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and Genetic Risk Factors for Acute Incident Venous Thromboembolism in Ambulatory Patients With COVID-19

Abstract: Key Points Question What is the 30-day acute risk of venous thromboembolism (VTE) among ambulatory patients with COVID-19, and what are the clinical and genetic risk factors predisposing them to developing post–COVID-19 VTE? Findings In this retrospective cohort study of 18 818 outpatients with COVID-19 and 93 179 propensity score–matched noninfected participants, a higher VTE incidence was observed in the former (hazard ratio, 21.42); however, this risk wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 40 publications
10
68
3
1
Order By: Relevance
“…After SARS-Cov-2 infection, as with other viral infections, a series of persistent symptoms have been described for COVID-19, called post-COVID syndrome or long-term COVID [27]. Although none of the studied patients with genetic alterations had thrombophilic events at the time of sample collection and considering that those with D-dimer alterations were treated prophylactically with anticoagulant therapy, individuals with hereditary thrombophilia are at greater risk of developing a thrombolytic event after infection , more precisely within 30 days after a positive diagnosis for SARS-CoV-2, than those who do not have any polymorphisms in any of the factors or genes studied here [28]. As observed, high values of D-dimer are, by themselves, a risk factor for the development of thrombosis.…”
Section: Discussionmentioning
confidence: 80%
“…After SARS-Cov-2 infection, as with other viral infections, a series of persistent symptoms have been described for COVID-19, called post-COVID syndrome or long-term COVID [27]. Although none of the studied patients with genetic alterations had thrombophilic events at the time of sample collection and considering that those with D-dimer alterations were treated prophylactically with anticoagulant therapy, individuals with hereditary thrombophilia are at greater risk of developing a thrombolytic event after infection , more precisely within 30 days after a positive diagnosis for SARS-CoV-2, than those who do not have any polymorphisms in any of the factors or genes studied here [28]. As observed, high values of D-dimer are, by themselves, a risk factor for the development of thrombosis.…”
Section: Discussionmentioning
confidence: 80%
“…During the pandemic, it was demonstrated that thrombotic events tend to occur early in the clinical course of COVID-19 [ 54 ]. Moreover, in the outpatient setting, the incidence of VTE is higher among outpatients with certain characteristics (older age, male sex, obesity, inherited thrombophilia, no or partial vaccination) [ 55 ]. In this context, early initiation of thromboprophylaxis in outpatients with adverse prognostic factors for severe disease (candidates for hospitalization) and increased VTE risk could be regarded as a reasonable approach.…”
Section: Results—key Questions and Practical Recommendationsmentioning
confidence: 99%
“…21,22 Importantly, the polygenic risk for conventional VTE was remarkably retained for COVID-19-related VTE, which echo the finding in our previous study showing that the monogenic such as factor V Leiden mutation also consistently predisposed post-COVID-19 VTE complications. 6…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Importantly, the polygenic risk for conventional VTE was remarkably retained for COVID-19related VTE, which echo the finding in our previous study showing that the monogenic such as factor V Leiden mutation also consistently predisposed post-COVID-19 VTE complications. 6 The role of genetics in variable COVID-19 representations is not yet well-understood. Although a large genome-wide association study (GWAS) was performed for COVID-19, it focused on SARS-COV-2-induced critical respiratory complications.…”
Section: Findings In Contextmentioning
confidence: 99%
See 1 more Smart Citation